1988
DOI: 10.1007/bf02536221
|View full text |Cite
|
Sign up to set email alerts
|

Formation of trimers of α‐tocopherol and its model compound, 2,2,5,7,8‐pentamethylchroman‐6‐ol, in autoxidizing methyl linoleate

Abstract: The reaction products of alpha-tocopherol and its model compound, 2,2,5,7,8-pentamethylchroman-6-ol, during the autoxidation of methyl linoleate at 37 C were investigated. Two isomeric trimers were obtained as the major reaction products of alpha-tocopherol, and a trimer was obtained as that of its model chroman. The structure of each trimer has been characterized by IR, UV, 1H and 13C NMR, and mass spectroscopy. The 13C NMR spectra showed the presence of a quaternary carbon atom and a carbon atom bearing two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 19 publications
4
42
0
Order By: Relevance
“…In order to check this hypothesis, we searched for the presence of 5a-methoxytocopherol (30) after methanolysis of NaBH 4 -reduced and non-reduced lipid extracts obtained from cells of Emiliania huxleyi s t r a i n T W P 1 a n d Chrysotila lamellosa strain HAP17. The detection of significant amounts of this methanolysis product of trimers (Yamauchi et al, 1988) in these extracts (Nassiry et al, 2009) well supported the presence of such trimeric oxidation products of vitamin E in these algae.…”
Section: Vitamin Esupporting
confidence: 57%
See 2 more Smart Citations
“…In order to check this hypothesis, we searched for the presence of 5a-methoxytocopherol (30) after methanolysis of NaBH 4 -reduced and non-reduced lipid extracts obtained from cells of Emiliania huxleyi s t r a i n T W P 1 a n d Chrysotila lamellosa strain HAP17. The detection of significant amounts of this methanolysis product of trimers (Yamauchi et al, 1988) in these extracts (Nassiry et al, 2009) well supported the presence of such trimeric oxidation products of vitamin E in these algae.…”
Section: Vitamin Esupporting
confidence: 57%
“…However, methanolysis of the residues obtained resulted to the formation of high amounts of 5a-methoxytocopherol (30) arising from the methanolysis of the ketal group of trimers (Fig. 12) (Yamauchi et al, 1988). ESI-TOF MS analyses of oxidation products were also carried out in order to confirm the presence of high proportions of trimers (Nassiry et al, 2009).…”
Section: Vitamin Ementioning
confidence: 99%
See 1 more Smart Citation
“…It has been determined that c!-tocopherol is the most efficient chain-breaking antioxidant among the four isomers. cY-Tocopherol also can react with alkoxyl radicals (Gardner et al, 1972;Kaneko & Matsuo, 1985) or undergo self-coupling to form dimers and trimers (Csallany et at, 1970;Yamauchi et al, 1988). When oxygen is present in trace amounts, c!-tocopherol can react directly with alkyl radicals (Evans et al, 1992;Yamauchi et al, 1993).…”
Section: A-tocopherol As the Free Radical Scavengermentioning
confidence: 99%
“…Figure 2 shows the possible pathways for the reactions of c!-tocopherol with lipid free radicals. It has been reported that the products of a-tocopherol (1) formed under mild conditions of autoxidation are a-tocopherylquinone (4), c!-tocopherol spirodiene dimer (6), and c!-tocopherol trimer (7) (Csallany et al, 1970;Yamauchi et al, 1988). However, the other reaction products might also be formed during the autoxidation of unsaturated lipids.…”
Section: A-tocopherol As the Free Radical Scavengermentioning
confidence: 99%